A cobalt free triple charge conducting Sm0.2Ce0.8O2-δ-Ba0.5Sr0.5Fe0.8Sb0.2O3-δ heterostructure composite cathode for protonic ceramic fuel cell. Issue 2 (15th January 2023) - Lu, Yuzheng; Mushtaq, Naveed; Yousaf Shah, M.A.K.; Irshad, Muhammad Sultan; Rauf, Sajid; Yousaf, Muhammad; Zhu, Bin
Abstract: Protonic ceramic fuel cells (PCFCs) are considered more capable of operating at low temperature than solid oxide fuel cells (SOFCs) e.g., at 300–600 ° C because of low activation energy associated with proton transport if suitable cathodes can be developed. Herein, we have developed a cobalt-free triple charge conducting (oxygen ion, proton and electron-hole) Sm 0.2 Ce 0.8 O 2- δ -Ba 0.5 Sr 0.5 Fe 0.8 Sb 0.2 O 3- δ (SDC-BSFSb) heterostructure composite for PCFC cathode. The SDC-BSFSb exhibit very low-area-specific resistance with large oxygen reduction reaction (ORR) activity over barium-ceria-based proton conducting perovskite-oxide electrolytes. We have demonstrated high-power densities of 705 mW-cm 2 for a button-sized PCFC at 550°C using H2 /air fuels, and even with possible operation at 400°C. Various spectroscopic measurements such as X-ray photoelectron, U-visible, Raman, and Density Functional Theory (DFT) calculations were employed to understand the improved ORR electrocatalyst function of SDC-BSFSb heterostructure composite for PCFCs cathode. It is found that SDC-BSFSb effectively showed enhanced ionic and electronic properties to exhibit high ORR at the interface of SDC and BSFSb particles. The results can further help to develop functional cobalt-free electro-catalysts for LT-PCFCs/LT-SOFCs and other related applications. Graphical abstract: Image 1